COMPARATIVE ANALYSIS OF ISLAMIC BANKING FINANCIAL PERFORMANCE BEFORE AND DURING THE COVID 19 PERIOD IN INDONESIA - Nofinawati N; Abdul Nasser Hasibuan; Dinda Sildiya; Ferdy Kurniawan (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Purpose: This research has objective to compare the Islamic banking financial performane between before and during the Covid 19 period and to specify the variables that determine financial performance such as CAR, NPF, FDR, and Net Profit.Research Methodology: Data analysis tools in this research used quantitative descriptive analysis which takes its data from the www.ojk.go.id at Islamic banking statistic, 6 month before covid 19 and 6 month during the covid 19 period. The data management by using quantitative descriptive study which means to analysis and describe a situation or phenomenon.Findings: the conclusion of this reseach is the existence of some differences in the magnitude of the ratios of Islamic banking financial performance before and during the covid 19 period in Indonesia.Originality: The result of this research is useful for improving Islamic banking performance in Indonesia.